Asean’s function in handling the Covid-19 pandemic - Saptopo Bambang Ilkodar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article examines ASEAN’s function and the effectiveness of that function in handling the COVID-19 pandemic. The author examines this problem because there is a gap that has no explanation, namely between the excellent performance of ASEAN member countries in handling the COVID-19 pandemic on the one hand and the lack of ASEAN functions in handling the pandemic. If ASEAN does not function much in handling the COVID-19 pandemic, why are its member countries performing better than countries in Europe and Latin America? The author uses a regionalism framework and finds four things that affect ASEAN’s function in handling the COVID-19 pandemic, namely: the level of member trust in regional organisations, the level of complexity of problems, the involvement of global organisations, and the amount of autonomy of regional organisations compared to member countries.